2012
DOI: 10.5772/54750
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Software for Customer Co-Creation: Does it Change the Practice for Innovation?

Abstract: This article investigates a customer co-creation project at the front end of the innovation process at a large well-known Italian food manufacturer, which is enabled by social media. The purpose is to shed light on the role of such technology in transforming the characteristics of the FEI, in terms of boundaries and knowledge distance: what type of innovation ideas – exploratory or exploitative – does the practice enable? Could social media be used to manage the explore-exploit paradox, thus transforming the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
0
20
0
2
Order By: Relevance
“…However, only a few studies investigate the use of social media for customer co-creation in open innovation and thus the mechanics of social media for cocreation is less understood [57]. Martini et al [76] conducted a case study with a large Italian food manufacturer and examined this company's customer co-creation practice enabled by social media. They found that this company used social media tools to engage customers in generating both incremental and radically innovative ideas.…”
Section: Social Media and Co-creationmentioning
confidence: 98%
See 2 more Smart Citations
“…However, only a few studies investigate the use of social media for customer co-creation in open innovation and thus the mechanics of social media for cocreation is less understood [57]. Martini et al [76] conducted a case study with a large Italian food manufacturer and examined this company's customer co-creation practice enabled by social media. They found that this company used social media tools to engage customers in generating both incremental and radically innovative ideas.…”
Section: Social Media and Co-creationmentioning
confidence: 98%
“…More and more organizations are trying to leverage the power of social media for innovation. By engaging employees and customers in creating new products/services or improving existing products/services, organizations can enhance their innovation performance, gain a deeper understanding of customer behaviors and desires, adapt more quickly to changing trends, and achieve sustainable competitive advantages [8,76,94]. However, due to the novelty of social media and the complexity of innovation process, many firms are unclear about how best to use social media to facilitate innovation and achieve useful outcomes [77].…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Istoriškai susiklostė, kad įmonės ir kliento sąveika orientuota į du 3 lentelė. Socialinių medijų klasifikacija pagal socialinį dalyvavimą / medijų gausumą ir savęs pristatymą / atskleidimą (Kaplan, Haenlein 2010) Socialinės medijos suteikia galimybę vartotojus pasiekti greičiau, efektyviau ir mažesne kaina, nei naudojant tradicines bendravimo ir rinkodaros priemones, tokias kaip skrajutės, televizijos reklamos ir transliacijos (Martini et al 2012). Gallaugher ir Ransbotham (2010) pateikė esminius pokyčius ryšiuose naudojant tradicines medijas ir dabartines socialines medijas.…”
Section: Socialinės Medijos Versle Jų Naudaunclassified
“…A recent and notable development with CoIN is the application of social technologies to engage actors through social mechanisms [3,15,18,29,38]. Distinctive from early open innovation approaches, the application of social mechanism in co-innovation represents a new business model enabled by social media technology platforms [1,38].…”
Section: Introductionmentioning
confidence: 99%